Decree no. 418/2016 on approving profits / losses difference resulting from procuring foreign currency upon determining the income tax base = قرار وزاري رقم 418 لسنة 2016 بشأن اعتماد فروق أرباح / خسار تدبير العملة الأجنبية عند تحديد وعاء ضريبة الدخل - Egypt. Ministry of Finance. The Egyptian Customs Authority (2025)
Ministry of finance decree no. 418 of the year 2016 on approving profits / losses differences resulting from procuring foreign currency upon determining the income tax base وزارة المالية قرار رقم 48 لسنة 2016 بشأن اعتماد قروق ارباح / خسائر تدبير العملة الأجنبية عند تحديد وعاء ضريبة الدخل